Two special valentines - McDonnell, Janet, 1962-; McCallum, Jodie (Chicago : Childrens Press, 1994)
Kevin and James are so involved in making each other valentines that they almost stop being friends. Includes handicrafts.
2.7
K-3
Keywords: Friendship -- Fiction; Handicraft; Valentine's Day -- Fiction; Friendship -- Fiction; Handicraft; Valentine's Day -- Fiction